Proceedings of the 25th Polar Libraries Colloquy: Papers presented at the 25th Polar Libraries Colloquy, hosted by the British Antarctic Survey and Scott Polar Research Institute, Cambridge, UK, 30th June – 4th July 2014. ... : PLC Proceedings 25 ... - Gray, Andrew (University of Alberta Library, 2014)
Papers presented at the Polar Libraries Colloquy June 30 - July 4, 2014 ...